(untitled) (Eurasian Journal of Ecology, 2016)
Study of nutritional requirements of the fish is necessary when solving a number of theoretical and applied assignments associated with artificial regeneration offish resources, assessment of damage incurred during the technogenic impact or directed formation of internal water basins ichthyofauna. Conducted surveys will allow to approach the issue of volume assessment of artificial reproduction ensuring regeneration and further formation of the beluga reserves in compliance with products of used fodder resources.